Phytochemical characterization of extracts of the mesocarp of Bactris gasipaes and evaluation of its antioxidant power for pharmaceutical dermal formulations - Madrigal Redondo, German (2019)
The Bactris gasipaes is a native palm from Central America which its fruit is known as pejibaye, its wood is also used for the manufacture of various utensils, the marrow of its tender stems is edible and it is called palmetto, it is used in the preparation of salads and other dishes. The pejibaye is cultivated in Costa Rica and part of the diet, this due to its high content of starch and mainly by content of antioxidant substances. The objective of the present study is to identify the main phytochemical groups and quantify the main markers in order to associate them with cosmetic or medicinal functions in pharmaceutical products. Materials and Methods: The mature fruits of Bactris gasipaes were peeled and separated the seeds of the mesocarp, were dried, milled and subdivisions were made with low, medium and high polarity solvents, then a phytochemical screening was carried out according to the Guidelines for the Quality Control of Products of Natural Origin of the World Health Organization, additionally the antioxidant properties were evaluated, the concentration of total phenols, total carotenoids content, the content and type of saturated and unsaturated fatty acids and the physicochemical properties of the aqueous extract were determined. The study found a low concentration of phenolic compounds such as condensed and non-condensed tannins and the main phytochemical groups such as: carotenoids, terpenes, fats, carbohydrates and alkaloids and the absence of Anthocyanins. The antioxidant power that was 45.56 ± 1.96 g/mol Trolox Eq/g dry fruit, an EC 50 0.293 mg/Lfor the mesocarp oil, the total phenols found are 0.628 ± 0.12 mg/Gof dry sample (equivalents of Gallic acid), which shows that the main antioxidant components are lipophilic, so they can be useful in formulations such as emollients, anti-aging effect, anti-wrinkle, nourishing and moisturizing for the skin, and as a sunscreen. The mesocarp oil contains unsaturated fats (78.6% ± 1.2 µg/g): oleic, linoleic and Palmitoleic and Palmitic acid, respectively 58.3 ± 1.8, 14.5 ± 1.2, 4.5 ± 0.3 and 20.8 ± 1.4 µg/g. The acidity index is 4.32 ± 0.10 which is beneficial to maintain the cutaneous acid mantle and thus favor the normal flora of the skin, although this property represents a challenge in the formulation of Carbomer-based gels. The aqueous extract is hyperosmotic, 2333 ± 9.54 mOs/kg, and has a high electrical conductivity (1492 ± 5.56 S/cm) due to the presence of polyelectrolytes and a high concentration of reducing sugars according to the obtained brix degrees (13.45 ± 0.01), finally mesocarp oil at 0.1% w/w shows an absorption of ultraviolet radiation of 25% at wavelengths between 260 nm and 400 nm, which could also be useful for formulating compositions for sun protection